Positioning Theory for English-Medium Instruction (EMI) praxis: Insights and implications for teaching and research - Hayriye Kayi-Aydar; Angel Steadman (Ibérica, 2021)
Developed as a socio-constructivist theory with the aim of understanding discursive construction of selves, Positioning Theory has been applied to the analysis of conversations and narratives across disciplines. This paper provides an overview of Positioning Theory developed by Rom Harré and his colleagues and describes the basic concepts and principles of the theory. By illustrating how it has been applied to studies in contexts that involve English language learners or teachers, the paper identifies ways that Positioning Theory may positively impact classroom practice and outlines areas for further research that EMI classroom practitioners can carry out. A number of practical guidelines for conducting positioning analysis are also offered.